Housing technology in Iraq - Mohammed hasan, Nagham Khalid; Rasheed Almullah Huish, Luay Taha Mohammed (Al-Adab Journal, 2020)
Iraq has demonstrated a race to provide advanced technology for housing since the dawn of time and until the end of the last century. In our research, we review the technology of systems, elements and building materials in the field of housing and an overview of this achievement in order to benefit from these experiences and news in their construction in order to know the areas of failure and success so that we can make the right decision about the appropriate technology for housing in Iraq, Starting from the diagnosis and follow-up to what is housing projects in Iraq and the materials involved in implementation that are not appropriate with the ecological climate in Iraq, as it does not provide the required thermal comfort inside the building, building materials are far from local materials that have effective equivalence with the climate and also with a lower cost And good quality comparable to what is foreign on building materials, Therefore, a historical sequence must be provided for everything that was presented in the building technology used in housing projects from the dawn of civilizations to our modern era in order to overcome the weaknesses and compliance with the positive aspects that would use technical building materials commensurate with housing projects in Iraq, and therefore because the building materials that It was used before the technology entered local materials, but with different technologies, depending on the specificity of the region, from the marshes to the traditional neighborhoods in the cities.